INNOVATIVE STRATEGIES FOR MANAGING DEVELOPMENT IN AN UNSTABLE ENVIRONMENT - Leonov, Ya.V. (SWorld-Ger Conference proceedings, 2024)
The article discusses the importance of innovative management strategies in an unstable environment. It focuses on the role of innovation in ensuring the sustainability and competitiveness of organisations. Various development management strategies are an